2009
DOI: 10.1111/j.1468-2982.2009.01859.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Topiramate for the Treatment of Patients with Chronic Migraine in the Presence or Absence of Acute Medication Overuse

Abstract: Chronic migraine has been linked to the excessive use of acute headache medications. Medication overuse (MO) is commonly considered the most significant risk factor for the progression of migraine from an episodic to a chronic condition. Managing MO is a challenge. Discontinuation of the acute medication can result in withdrawal headache, nausea, vomiting and sleep disturbances. This review summarizes the results from two similarly designed, randomized, placebo-controlled, multicentre studies of chronic migrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 42 publications
4
72
0
9
Order By: Relevance
“…The effect size was overall modest, however, with a mean reduction in monthly migraine days of 3.5 (versus placebo -0.2) and a numberneeded-to-treat of 12.5 [61]. Remarkably, the benefits of topiramate extended to the subgroup of patients who were overusing acute medications [62]. Topiramate use was also associated with a decreased number of monthly days of acute medication use (-3 days in the topiramate group versus -0.7 days in the placebo group), but this difference was not statistically significant.…”
Section: Topiramatementioning
confidence: 96%
“…The effect size was overall modest, however, with a mean reduction in monthly migraine days of 3.5 (versus placebo -0.2) and a numberneeded-to-treat of 12.5 [61]. Remarkably, the benefits of topiramate extended to the subgroup of patients who were overusing acute medications [62]. Topiramate use was also associated with a decreased number of monthly days of acute medication use (-3 days in the topiramate group versus -0.7 days in the placebo group), but this difference was not statistically significant.…”
Section: Topiramatementioning
confidence: 96%
“…This was due to the awareness that prophylactics during overuse do not reduce headache frequency. Only recently it was shown that topiramate is effective even in patients overusing medication (16).…”
Section: Discussionmentioning
confidence: 99%
“…6 Two larger, randomized, double-blind, placebo-controlled, parallel-group clinical trials were performed with topiramate in patients with CM. Significant reduction in the mean monthly rate of migraine/migrainous days (6.4 Ϯ 5.8) compared to placebo (4.7 Ϯ 6.1; p ϭ 0.010) and a mean reduction from baseline of migraine days per month (5.6 Ϯ 6.0) compared to placebo (4.1 Ϯ 6.1; p ϭ 0.032) was observed in the United States, 7 whereas reduction in mean monthly migraine days (Ϫ3.5 Ϯ 6.3) was noted compared to placebo (0.2 Ϯ 4.7 p ϭ 0.02) in a study conducted in the European Union. In this study, patients with acute MO reported mean monthly reduction in migraine days by 3.5 Ϯ 7.1 days, which was significant compared to placebo with an increase of 0.8 Ϯ 4.8 days ( p ϭ 0.03).…”
Section: Treatment Options For Chronic Migrainementioning
confidence: 98%